Perfil motivacional de los funcionarios de la empresa comercializadora de hierbas aromáticas Fresh Herbs: un estudio de caso (2008)
In this investigation the motivational profile of the civil employees of the commerce company of aromatic grass Fresh Herbs was established. It was developed under a correlational descriptive design of the scores of the 15 internal and external motivational factors and the favorite averages to obtain the repayments waited for in the work, from the Questionnaire of Work Motivation (CMT- Cuestionario de Motivación para el trabajo) elaborated by Toro (1985), with the socio-demographic variables of the participants: age, gender, position and antiquity in the company. The questionnaire was administered to a sample of twenty civil employees who directly are related to the company. The results showed that pay is the most significant motivational factor between the participants, factor that displays highest average, whereas the content of the work is the factor with the lowest average. From this, some recommendations that the organization can implement to improve the quality of life in the work, also, to obtain benefits for the personnel in their competitive development and the production, were considered. Key words: motivation, motivational profile, work motivation, CMT.